Faktor-faktor yang Memengaruhi Indeks Kualitas Lingkungan Hidup di Indonesia, 2017-2021 - Luhung, Suci Utami Adi; Yuniasih, Aisyah Fitri (Seminar Nasional Official Statistics, 2023)
Economic development is closely related to environmental degradation. Indonesia's Environmental Performance Index score is only 28.2, which ranks at the bottom compared to ASEAN-6 countries. Indonesia's Environmental Quality Index (EQI) tends to fluctuate. In fact, the Water Quality Index (WQI) and Land Cover Quality Index (LQI) are less than 70, which means they are in the moderate category and tend to stagnate. Therefore, this study aims to determine the general description of environmental quality as approximated by the EQI and the factors that are thought to influence it and analyze what factors affect EQI in Indonesian provinces in 2017-2021. Panel data regression analysis was applied in this study. The result of this study is that GRDP per capita and GRDP of processing industry have a significant negative effect, while GRDP per capita quadratic, urban population, ICT, and financial development have a significant positive effect on the EQI in Indonesia.